The Normalization of Lying in the Post-Truth Era: A Moral-Philosophical Analysis of Social Validation and Digital Culture - Sulistyawati, Felisa; Nisa, Zahra Khoiru (PUBLICUS: Jurnal Administrasi Publik, 2026)
Honesty has traditionally been regarded as a fundamental moral virtue that sustains trust and ethical responsibility in social life. However, in the contemporary post-truth era, honesty increasingly loses its moral authority as lying becomes normalized within everyday social practices, particularly in digitally mediated environments. This study aims to examine the normalization of lying from a moral-philosophical perspective by analyzing how pragmatic ethical reasoning, digital culture, and structural social pressures contribute to the erosion of honesty as a shared moral value. Employing a qualitative research design with a philosophical and interpretative approach, this study relies on a systematic literature review of scholarly works on moral philosophy, post-truth culture, and digital ethics published over the last decade. The analysis reveals that moral evaluation in modern society has shifted from principled ethical obligations toward outcome-oriented and pragmatic considerations. Social media platforms further accelerate this shift by rewarding visibility, performativity, and symbolic success, thereby legitimizing deceptive self-presentation and strategic manipulation. Additionally, economic competition and performance-driven success standards encourage moral justification, allowing lying to be perceived as a rational and socially acceptable practice. The study concludes that the normalization of lying poses significant ethical risks by undermining moral integrity, weakening social trust, and threatening social cohesion. Reaffirming honesty as a core moral commitment is therefore essential for addressing the moral challenges of the post-truth era.